Synthesis of cross-linked pine cone biosorbent and its applications in industrial wastewater treatment - Kupeta, Albert Jerry Kafushe (My University, 2014)
The widespread use of phenols and phenolic derivatives in industrial applications has resulted in their discharge as part of industrial wastewater. These chemicals are toxic and need to be removed from the aqueous environment. Amongst the available pollutant removal technologies, adsorption has been widely used due to its simplicity, ease of operation, cost-effectiveness and ability to sequester pollutants at very low concentrations. Different adsorbents have been applied for removal of phenols and their derivatives. Use of agricultural waste as adsorbents seems to offer a much cheaper alternative in pollutant removal. This study examines the synthesis of a hydrophobic biomaterial composite by cross-linking of Fenton treated pine cone and applying the prepared adsorbent for 2-nitrophenol removal from aqueous solution. Pine cone biomass, in its raw and modified forms was tested for its ability to remove 2-nitrophenol from simulated industrial wastewater. The experimental procedure is divided into two main parts: (1) pine cone modification using Fenton’s reagent and 1.6-hexamethylene diisocyanate and (2) application of the prepared hydrophobic adsorbent for 2-nitrophenol removal from wastewater. Fenton’s reagent was used to remove pigments, extractives and other soluble organic compounds from the raw pine. FTIR spectroscopy showed an increase in magnitude of oxygenated surface groups which resulted in a decrease in pHpzc. The effect of Fenton treatment on further modification of the pine biomass via cross-linking using 1.6-hexamethylene diisocyanate was investigated. Optimum reaction variables for the cross-linking using dibutyltin dilaurate as catalyst under an inert nitrogen gas atmosphere in anhydrous hexane solvent were determined using FTIR spectroscopy. Success of the cross-linking procedure was confirmed by use of analytical techniques (XRD, TGA, SEM, EDX and BET surface area) and weight percent gain calculations. Pine and modified pine biomass were tested for their ability to sequester 2-nitrophenol via batch adsorption technique. The effect of pine modification on affinity for the biosorbate was investigated. The mechanism of the adsorption process was determined via use of kinetic, diffusion and equilibrium isotherm models. Two error functions (coefficient of determination and percent variable error) were employed to substantiate the model showing a good fit to the experimental adsorption data. The experimental adsorption kinetic data was fit to the pseudo-first-order and pseudo-second-order kinetic models. Due to the large size of the pollutant molecules diffusion process analysis was also conducted. The effect of pine modification on kinetic and diffusion parameters was determined. The experimental equilibrium adsorption data was fit to the Freundlich, Redlich-Peterson and Hill isotherm models. The initial shapes of the adsorption isotherms for 2-nitrophenol adsorption onto pine and modified pine biomass determined the type of equilibrium isotherm models to fit the experimental data to. Thermodynamic parameters were calculated to determine the spontaneity, feasibility and energy changes associated with the adsorption process. The degree of disorder at the solid/liquid interface after the adsorption was determined. The effect of temperature on the adsorption process was used to show whether the adsorption is physical or chemical. The effect of pine modification on equilibrium isotherm parameters was determined. The study is divided into seven chapters: Chapter 1: The chapter covers the introduction, problem statement, aim and objectives of the research. It gives an insight into the research project. Chapter 2: The literature review of pollutants in industrial wastewater and methods of their removal is dealt with in this chapter. Adsorption is introduced as an alternative technique for pollutant removal from aqueous systems. An in-depth review of various adsorbents (including pine cone), their merits and limitations are also discussed together with methods of modifying and use of modified adsorbents. Equilibrium, kinetic and thermodynamic models used to treat adsorption experimental data are presented. Chapter 3: The experimental procedures on the synthesis, characterization and application of the hydrophobic biosorbent in the removal of 2-nitrophenol from aqueous solution are presented. Kinetic and equilibrium experiments are described in detail. Chapter 4: It describes the first part of the results and discussions. The chapter focuses on optimization of reaction variables and characterization (using various analytical techniques) of the hydrophobic biomaterial composite. Chapter 5 The chapter discusses the second part of the results. It focuses on magnitude of surface charge, pHpzc and kinetic studies. Fitting of the adsorption experimental data to kinetic and diffusion models is presented together with the error functions. Chapter 6 The chapter discusses part three of the results on equilibrium studies. The adsorption experimental data is fitted to equilibrium isotherm equations and error determination is presented. Thermodynamic parameters are calculated and interpreted. Chapter 7: Conclusion and recommendations are presented. The optimum reaction variables for cross-linking of Raw and Fenton treated pine cone were determined using FTIR analysis and found to be: 0.2 g pine biomass, 3.5 cm3 1.6-hexamethylene diisocyanate cross-linker, 50 cm3 anhydrous hexane solvent, 1.5 cm3 dibutyltin dilaurate catalyst, temperature of 50 °C and a reaction time of 4 hours. The pine surface showed an increase in phenolic, lactonic and carboxylic acid groups due to the modification. The pHpzc showed a decrease due to modification of the pine cone biomass. The pHpzc values for the pine and modified pine cone biomass were found to be: Raw = 7.49, Raw-HMDI modified = 6.68, Fenton treated pine = 5.40 and Fenton-HMDI modified = 6.12. The optimum pH for the adsorption of 2-nitrophenol onto raw pine and modified pine cone biomass was determined to be 6. The optimum adsorbent dosage was determined as 1.5 g/dm3. The adsorption kinetics show a good fit with the pseudo-second-order model. This suggests that surface adsorption is the controlling step in the adsorption of 2-nitrophenol onto pine cone biomass. The analysis of diffusion processes showed that the initial rapid stage during the adsorption is due to external mass transfer processes. The adsorption experimental data also showed that pore diffusion was rate-limiting amongst the diffusion processes. Pine modification using Fenton’s reagent and 1.6-hexamethylene diisocyanate increased magnitude of kinetic and diffusion parameters. Experimental data for 2-nitrophenol adsorption onto pine and modified pine cone biomass showed better correlation with the Redlich-Peterson and Hill isotherm models and poor correlation with the Freundlich isotherm model. This suggests that the mechanism does not show complete multilayer coverage with cooperative phenomena between adsorbate molecules. Thermodynamic parameters showed that the adsorption is feasible, spontaneous, and exothermic and results in a decrease in degree of disorder at the solid/liquid interface. An increase in temperature resulted in a decrease in adsorption capacity showing that the adsorption is physical. Pine modification using Fenton’s reagent and 1.6-hexamethylene diisocyanate increased magnitude of kinetic, diffusion and isotherm parameters. The kinetic and equilibrium results show that the adsorption of 2-nitrophenol onto pine cone biomass follows the order: Fenton treated-HMDI > Fenton treated > Raw-HMDI > Raw. Hence, it can be concluded that Fenton treatment and HMDI cross-linking modification did increase the adsorptive capabilities of the pine cone biomass.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences) -- Vaal University of Technology
Keywords: Phenols; Phenolic derivatives; Industrial wastewater; Pollutant removal technologies; Adsorption; Agricultural waste; Hydrophobic biomaterial composite; 2-Nitrophenol; Pine cone biomass; Fenton treated pine cone; 622.5; Sewage -- Treatment; Phenols -- Absorption and adsorption; Bioorganic chemistry; Agricultural wastes -- Environmental aspects